2013
DOI: 10.1002/ar.22785
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Human Ilium: The Anomalous Sacroiliac Junction

Abstract: Despite the major anatomical importance of the human ilium in medicine and forensic investigations, little is understood about its pattern of growth. This study was conducted to investigate the changes in the surface area of the human ilium from birth through to adolescence in 80 human ilia. A photographic image of the pelvic surface of each bone was taken and examined using an image quantification package. The surface areas of four regions of interest were quantified: the auricular, post-auricular (PA), iliac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…This role is mainly played by the iliac tuberosity and the proximal bone prominence of sacrum which in vivo are in close contact with each other. This interpretation is consistent with the results of a study on the growth of human ilium showing that the extra-articular portion is considerably larger than the articular surface, a disparity that might be a response to the load placed on the extra-articular portion by the posterior sacroiliac ligaments [33].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This role is mainly played by the iliac tuberosity and the proximal bone prominence of sacrum which in vivo are in close contact with each other. This interpretation is consistent with the results of a study on the growth of human ilium showing that the extra-articular portion is considerably larger than the articular surface, a disparity that might be a response to the load placed on the extra-articular portion by the posterior sacroiliac ligaments [33].…”
Section: Discussionsupporting
confidence: 74%
“…The mechanical function of the SIJ is to allow the movements between the auricular surfaces of the sacrum and ilium, that have been named nutation (forward nodding) and counternutation (backward nodding), to be accomplished. A further function, however questioned [33], is a direct weight transfer from the axial to appendicular skeleton. This role is mainly played by the iliac tuberosity and the proximal bone prominence of sacrum which in vivo are in close contact with each other.…”
Section: Discussionmentioning
confidence: 98%
“…In a study of the changes in the surface of the human ilium from birth to adolescence, Yusof et al. () found that the surface area of the ASI increased rapidly from soon after birth until around 4 years of age. This period overlaps with the stage of human development in which children progress from a supine, non‐weight‐bearing environment to becoming capable of bipedal walking, and Yusof et al.…”
Section: Discussionmentioning
confidence: 99%
“…We found that it can be characterized in terms of (i) size, (ii) concavity of the posterior border and (iii) amount of undulation. In a study of the changes in the surface of the human ilium from birth to adolescence, Yusof et al (2013) found that the surface area of the ASI increased rapidly from soon after birth until around 4 years of age. This period overlaps with the stage of human development in which children progress from a supine, non-weight-bearing environment to becoming capable of bipedal walking, and Yusof et al (2013) suggest that the structure of the ASI may thus change in preparation for bipedalism and to maintain it.…”
Section: Characteristics Of the Three-dimensional Morphology Of The Asimentioning
confidence: 99%
See 1 more Smart Citation